Pistorius ineligible for the Olympic Games: the right decision - Lippi, G.; Mattiuzzi, C. (British Journal of Sports Medicine, 2008)
Oscar, world record holder in the 100, 200 and 400 m Paralympic events, had a dream—to compete in the Beijing Olympics by qualifying for South Africa. In mid-January, however, his dream was dashed when the International Association of Athletics Federations (IAAF) outlawed his prosthetic racing blades; the International Olympic Committee upheld that decision.